Persepsi Perawat terhadap Implementasi Sistem Informasi Keperawatan Berbasis Komputer di Rumah Sakit - Rusnita, Rusnita (Barongko: Jurnal Ilmu Kesehatan, 2025)
Background: Implementation of computer-based nursing information systems in hospitals is an important part of the digitalization of health services. Nurses as the main users of the system have perceptions that can affect the effectiveness of its use. Objective: To determine nurses' perceptions of the implementation of computer-based nursing information systems in hospitals. Method: This study used a quantitative descriptive approach with a survey technique using a questionnaire. A sample of 100 nurses was selected by purposive sampling in one of the general hospitals in Indonesia. Results: Most nurses (72%) had a positive perception of computer-based nursing information systems. The most appreciated aspects were efficiency of documentation time (85%), ease of access to patient data (80%), and increased accuracy of documentation (77%). Conclusion: Nurses' perceptions of computer-based nursing information systems were positive, but there were still challenges such as less than optimal training and technical problems.